Aftermath : Genocide, Memory and History - Auerbach, Karen (History, 2015)
Aftermath: Genocide, Memory and History examines how genocide is remembered and represented in both popular and scholarly memory, integrating scholarship on the Holocaust with the study of other genocides through a comparative framework. Scholars from a range of disciplines re-evaluate narratives of past conflict to explore how memory of genocide is mobilised in the aftermath, tracing the development and evolution of memory through the lenses of national identities, colonialism, legal history, film studies, gender, the press, and literary studies